2010
DOI: 10.1177/030089161009600404
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present and Future of the Cervical Cancer Screening in Latvia

Abstract: Traditionally in Latvia, most women request gynecological services for preventive and health promotion reasons or in the case of having a gynecological disease. So the overloaded general practitioners and the lack of involvement of gynecologists are one of the main obstacles to solve for implementing an organized screening program in Latvia. Moreover insufficient availability of quality-assured services and resources for cytology testing and other services of the program, and for monitoring and evaluating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Studies have shown that improperly collected cytological smears are in fault for false negative or false positive results. 6,7 In the current study, 42.9% (n=24) of invasive cervical cancer cases were detected in women who had had either annual visit to a gynecologist or visit once in a three years. For 32.2% (n=18) of patients to whom cancer was detected in late stage, the cytological examination interval was shorter than three years.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Studies have shown that improperly collected cytological smears are in fault for false negative or false positive results. 6,7 In the current study, 42.9% (n=24) of invasive cervical cancer cases were detected in women who had had either annual visit to a gynecologist or visit once in a three years. For 32.2% (n=18) of patients to whom cancer was detected in late stage, the cytological examination interval was shorter than three years.…”
Section: Discussionmentioning
confidence: 55%
“…6,7 Frequency of false positive and false negative results is equal for both methods. 6 Thus, the cytological test result depends on quality of the material and qualification of the cytotechnologist. Studies have shown that improperly collected cytological smears are in fault for false negative or false positive results.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations